Invisible countries : journeys to the edge of nationhood - Keating, Joshua (Yale University Press, 2018)
"A thoughtful analysis of how our world's borders came to be and why we may be emerging from a lengthy period of "cartographical stasis." What is a country? While certain basic tenets-such as the clear demarcation of a country's borders, and the acknowledgment of its sovereignty by other countries and by international governing bodies like the United Nations-seem applicable, journalist Joshua Keating's book explores exceptions to these rules, including "breakaway," "semi-autonomous," or "self-proclaimed" countries such as Abkhazia, Kurdistan, Somaliland, a Mohawk reservation straddling the U.S.-Canada border, and an island nation whose very existence is threatened by climate change. Through stories about these countries' efforts at self-determination, as well as their respective challenges, Keating reveals that there is no universal legal authority determining what we consider a country. He argues that although our current world map appears fairly static, economic, cultural, and environmental forces in the places he describes may spark change. Keating ably bridges history with incisive and sympathetic observations drawn from his travel and personal interviews with residents, political leaders, and scholars in each of these countries"--Publisher's description